2013
DOI: 10.1519/jsc.0b013e318267a35c
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses and Activity Profiles of Football Small-Sided Games

Abstract: The aim of this study was to identify the acute physiological responses and activity profiles of football small-sided games (SSG) formats. Ten professional football players participated in 4 variations of SSG (2-, 3-, 4-, and 5-a-side) with an intermittent regime involving 3 × 6-minute bouts with 1 minute of passive planned rest in which the heart rate (HR), rating of perceived exertion (RPE), activity profile, and body load were recorded. The higher percentage of maximum HR values were found in 2- and 3-a-sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
3
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 31 publications
(60 reference statements)
8
81
3
14
Order By: Relevance
“…The HR% values recorded in the following study, during the exercise of 3vs3, stands at 87,2±3,3% of HR max, are in agreement with other studies assessing the 3vs3, (performed with or without the presence of goalkeepers) that have reported percentages of max HR ranging between 87% and 89%. 16,18,25,33,34 This valuesare in agreement with another study that showed during an exercise conducted in 3vs3 "cage" modality, although with smaller subjects compared to those of this study, FC values equal to 88±2,7% of HR max.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The HR% values recorded in the following study, during the exercise of 3vs3, stands at 87,2±3,3% of HR max, are in agreement with other studies assessing the 3vs3, (performed with or without the presence of goalkeepers) that have reported percentages of max HR ranging between 87% and 89%. 16,18,25,33,34 This valuesare in agreement with another study that showed during an exercise conducted in 3vs3 "cage" modality, although with smaller subjects compared to those of this study, FC values equal to 88±2,7% of HR max.…”
Section: Resultssupporting
confidence: 92%
“…The RPE values of 3vs3 (17,5±0,7) are in agreement with other studies that, however, used a larger field, a greater playing time and different age subjects (3,34). The RPE values revealed during the 4vs4 (16,3±1,3) are in agreement with other studies carried out on young players.…”
supporting
confidence: 91%
“…A et al 19 , analisando jogadores adultos, demonstraram que a distância percorrida em "sprints" foi superior no JCR 3 vs 3 comparado aos JCRs 5 vs 5 e 2 vs 2. No presente estudo, não encontramos diferença na distância percorrida em "sprint" comparando os JCRs 3 vs 3 e 7 vs 7; porém, a distância percorrida em "sprint" em ambos os JCRs (44 ± 38 m; 38 ± 25 m) no presente estudo foram superiores às distâncias (10, No entanto, não podemos levar em consideração apenas a distância em "sprints" como característica de demanda física, pois ela é in uenciada pelo tamanho do campo.…”
Section: Tabela 2 -Distâncias Percorridas Em Alta Velocidade (Av) E Bunclassified
“…Em relação aos pequenos jogos, estudos frequentemente investigam respostas técnicas 13 , táticas 14 , físicas -associadas ao perfil motor -e fisiológicas 15 a partir de alterações nas configurações, i.e. tamanho do campo 13 , número de jogadores 13 , limitação de toques na bola 16 e superioridade numérica 17 .…”
Section: Introductionunclassified